MODEL PEMBELAJARAN MANDIRI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA KRISTEN - Zendrato, Novia Julita; Tandiongan, Fianus; Manik, Disetra Fiser (JOURNAL of THEOLOGICAL STUDENTS, 2024)
This study aims to determine how much influence the use of independent learning models has on student learning outcomes at SMK Negeri 1 Lotu. In this study researchers used quantitative research methods. was accepted because it was proven that the analysis of the data obtained by 0.794a was in the strong category, meaning that PAK teachers at SMK N. 1 Lotu had tried to apply the independent learning model to student learning outcomes. However, based on the findings, the researchers still found obstacles experienced by teachers and students in applying the independent learning model to learning outcomes (there are still some students who are not active and participate in the learning process).